Cover Picture: Ann. Phys. 10‐11'2013. Issue 10 (4th November 2013) - Blatt, Rainer; Bloch, Immanuel; Cirac, Ignacio; Zoller, Peter
<x xml:space="preserve">Abstract</x> Sketch of a quasi one‐dimensional Wigner crystal of mutually repelling quantum particles (e.g. ions) in a cigar‐shaped trap. Depending on the radial confinement, the equilibrium configuration is either a linear structure (top layer) or a zig‐zag structure (bottom layer). In the article by P. Silvi et al., a full characterization of such quantum phase transition is studied, through theory and numerical methods. Picture: P. Silvi et al., pp. 827–832 in this issue <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>